The Relationship between Work Motivation and Organizational Commitment of Employees at ABC Company Limited - Tuyla , Chanjira; Wonglek, Pusit; Anantarak, Phuwakorn (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed to 1) study the level of employees’ work motivation at ABC Company Limited, 2) study the level of employees’ organizational commitment at ABC Company Limited, and 3) study the relationship between the employees’ work motivation and organizational commitment at ABC Company Limited. The samples consisted of 285 employees from 5 departments, determined the sample size according to Krejcie and Morgan’s Table, with a 95% confidence level and ±5% acceptable error, and using stratified sampling. The instrument used for data collection was a questionnaire with an Index of item-objective congruence (IOC) between 0.67-1.00 and the overall reliability was 0.98. The statistics used for data analysis were mean, standard deviation, and hypothesis testing by Pearson’s product-moment correlation. The research results were as follows: 1) The level of employees’ work motivation at ABC Company Limited, overall, was at a moderate level. When considering each aspect found that the highest level of work motivation was the need for power, followed by the need for affiliation, and the need for achievement. 2) The level of employees’ organizational commitment at ABC Company Limited, overall, was at a moderate level. When considering each aspect found that the highest level of organizational commitment was trust and acceptance of organizational values and goals, followed by passion to maintain their organizational membership, and willingness to work with full effort for the organization, respectively. And 3) The overall employees’ work motivation was a positive relationship with organizational commitment at ABC Company Limited, at a high level with statistically significant at the level of .01.